The Unified State Exam in Russia: Problems and Perspectives - Denisova-Schmidt, Elena; Leontyeva, Elvira (International Higher Education, 2014)
Since 2009, all Russian students have had to pass the EGE (Unified State Exam), which serves as both school finals and university entrance examinations. The EGE was planned as an efficient instrument to counter corruption in university admission and to promote student mobility. Since its inception, the EGE has only fulfilled half of these goals: while mobility has increased significantly, corruption persists. The paper explains some of the reasons for this.